Legal Responsibility of Company as Issuers for Stock Value Decline Due to Lack of Information Disclosure Principles - Faradiba, Nona; Ginting, Budiman; Sidabariba, Burhan (JURNAL MERCATORIA, 2025)
This study aims to determine the role of legal protection regulations, as this protection is a right granted to investors given the numerous risks involved in stock trading, which can affect stock offerings. When investors sell a large number of company shares, the stock value can decline. Every investment carries a different level of risk, and stocks, as a high-risk, high-return investment instrument in the capital market, are no exception. Rational investors aim for investments that offer maximum returns with a certain risk or specific returns with minimal risk, based on individual preferences. This study uses a normative juridical research method, based on legal norms with a literature study approach. This research is descriptive, and qualitative data analysis methods are applied. The results show that companies, as issuers, can be held liable through civil, criminal, and administrative liability. In cases where false information is provided, liability for manipulation may arise under Article 78 paragraph 1 or for omitting material facts necessary to prevent misleading investors.